Impact of Aging on Urinary Excretion of Iron and Zinc. (January 2014) - Pfrimer, Karina; Micheletto, Rutinéia Fátima; Marchini, Julio Sergio; Padovan, Gilberto João; Moriguti, Julio cesar; Ferriolli, Eduardo
Project: Data about the influence of aging on urinary excretion of iron and zinc are scarce. The objective of the present study was to compare the concentration of zinc and iron in the urine of healthy elderly subjects and younger adults. Procedure: Seven healthy elderly subjects and seven younger adults were selected and submitted to biochemical, clinical, and nutritional tests. After a fasting period, 12-hour urine was collected for the determination of iron and zinc concentrations by graphite furnace atomic absorption spectrophotometry. Results: Urinary zinc and iron concentrations of the elderly subjects were not significantly different from that of younger adults. However, the total zinc and iron urinary clearance in 24 hours for the elderly was significantly higher compared with that of younger adults. Conclusion: There is an increase in urinary iron and zinc clearance with aging. The values reported in this manuscript may be used as references in future studies.